Metodologia para análise de risco: estudo em uma unidade de co-geração de energia de um shopping center de Macaé - Silberman, Tania Destefane de Araujo (2003)
In function of an increasing demand for information on the risk to which a community is exposed, the industry is self adjusting in order to give a reliable and responsible reply. lt is not enough to have and to operate a called reliable instailation, it is necessary the evidence. For a scientific evidence, based in modem techniques of inquiry and mathematical modeis, the industry adopted several techniques for the analysis of the associate iisk to íts instaNations. The present tisks analysis techniques quantify the operational risk and are able to submit it for the society acceptability. This work establishes a methodology for risk analysis in an energy cogeneration unit that uses natural gas as combustible, installed in a shopping center at Macaé. The scope of this study understands the use of risk analysis techniques as a tool for the risk analysis of a natural gas pipeline, sínce the act of receiving in the gas measurement station until the entrance of the co-generation building. The purpose of this study is to show that is possible and reliable to adopt this system as power plant in similar instaliations using natural gas. The denving result of this study allows to the responsible one for the instailation, to take decisions and steps of secunty prevention in order to assure the reliability of the refered instailation for the supposed population exposed to the risk.